Effect of Board Diversity on Firm Performance: Evidence from Malaysian non-Financial Listed Companies - Djerfi , Abderahmane; Louadj , Mounir (Finance and Business Economies Review, 2023)
The purpose of this paper is to investigate the impact of board diversity on firms' performance for non-financial companies. The paper statistically calculates the relationship between board diversity and performance for the period 2017-2020 using the perspectives of different theories and data collected on board composition in the 100 largest non-financial companies listed on Bursa Malaysia. The results showed that gender diversity was significantly and positively associated with Tobins'Q and ROA. BD_QUAL also had a strong negative correlation with Tobins'Q and ROA. The results also showed that AGE_CEO was significantly and positively associated with Tobins'Q and was not significantly associated with ROA.